2020
DOI: 10.24251/hicss.2020.622
|View full text |Cite
|
Sign up to set email alerts
|

Criteria as a Prelude for Guiding Taxonomy Evaluation

Abstract: Taxonomies are design science artifacts used by researchers and practitioners to describe and classify existing or future objects of a domain. As such, they constitute a necessary foundation for theory building. Yet despite the great interest in taxonomies, there is virtually no guidance on how to rigorously evaluate them. Based on a literature review and a sample of 446 articles, this study explores the criteria currently employed in taxonomy evaluations. Surprisingly, we find that only a minority of taxonomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…One criterion for assessing artifacts such as taxonomies is by evaluating their usefulness related to their intended purpose [ 111 , 116 ]. However, there are only very few taxonomy-specific evaluation guidelines [ 117 ], but multiple evaluation approaches can be applied in health informatics [ 118 - 120 ]. Szopinski et al [ 49 ] analyzed the various approaches researchers applied to evaluate taxonomies in the information system’s domain and demonstrated that the Delphi technique was hardly used.…”
Section: Resultsmentioning
confidence: 99%
“…One criterion for assessing artifacts such as taxonomies is by evaluating their usefulness related to their intended purpose [ 111 , 116 ]. However, there are only very few taxonomy-specific evaluation guidelines [ 117 ], but multiple evaluation approaches can be applied in health informatics [ 118 - 120 ]. Szopinski et al [ 49 ] analyzed the various approaches researchers applied to evaluate taxonomies in the information system’s domain and demonstrated that the Delphi technique was hardly used.…”
Section: Resultsmentioning
confidence: 99%
“…Evaluating the quality of the job descriptor taxonomies (taxons) is an important activity for ensuring useful classifications of jobs into job groupings that are similar in terms of skill, effort, responsibility, and working conditions. Szopinski et al (2019) and Stribling et al (2003) provide very helpful guidance on strategies and criteria for evaluating taxonomies. Similarly, I-O scientists and practitioners recognize the importance of evaluating the quality of taxonomic structures and the results of using those taxonomies.…”
Section: Importance Of Taxonomies For Classificationmentioning
confidence: 99%
“…Researchers developing a taxonomy have to identify potential use cases which also build the basis for evaluating the taxonomy later on [10], [11], [12], [13], [14], [15]. Currently, there exist several different VR locomotion taxonomies [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to providing insights into the evolution of the research field and the knowledge that has already been acquired, use cases can provide the basis for creating, choos-ing and evaluating taxonomies in a user-centred approach. Usefulness of taxonomies is one of the most common quality criteria [10] and is often evaluated based on use cases [11], [13], [14], [15]. To support this approach, we have extracted several use cases by extracting the goals described by the authors in the taxonomy publications, which were subsequently fused by several researchers.…”
Section: Introductionmentioning
confidence: 99%